Nasal adenocarcinoma as a suspected secondary malignant neoplasm in a cat previously treated for nasal lymphoma. Issue 1 (February 2020) - Callanan, Gabrielle F; Curran, Kaitlin M; Parachini-Winter, Cyril; Bracha, Shay; Spagnoli, Sean; Russell, Duncan S; Stieger-Vanegas, Susanne M; Griffin, Lynn; Leeper, Haley
Case summary: A case of nasal adenocarcinoma as a suspected secondary malignant neoplasm following definitive radiation therapy and multiagent chemotherapy for nasal lymphoma is described. An 11-year-old spayed female domestic shorthair cat was presented for a 3-week history of progressive facial swelling located over the nasal planum and extending to the medial canthus of the right eye. The cat was previously diagnosed with nasal lymphoma and treated with chemotherapy and definitive radiation 2.5 years prior. Although a definitive diagnosis could not be obtained via cytology, recurrent lymphoma was suspected based on the cat's history and recurrent clinical signs. A lymphoma-directed chemotherapy protocol was attempted, but no clinical response was achieved. The cat was euthanased owing to progressive clinical signs and a diagnosis of nasal adenocarcinoma was made on necropsy examination. Both the original diagnosis of nasal lymphoma and the secondary diagnosis of nasal adenocarcinoma were confirmed with immunohistochemistry. Relevance and novel information: Secondary malignant neoplasm following radiation therapy is infrequently reported in the veterinary literature. In the few reports that exist, most have described sarcoma development in the dog following radiation therapy. In the present report, we describe a cat with a suspected radiation-induced nasal adenocarcinoma that developed 2.5 years after definitive radiation treatment for nasal lymphoma.